(untitled) - Cotterell, Arthur (New York, 1993)
The book condenses into a short, highly readable book an immense amount of historical knowledge, placing this remarkable economic boom in its proper perspective - an Asia one. It ranges from the dawn of Chinese civilization, to the rise of the Mongols and the Manchus, to Japan's emergence as the first East Asia nation to develop an industrial economy. It also examines America's setbacks in the Korean and VietNam War, Japan's rise as an economic superpower, and the recent histories of Thailand, Cambodia, Laos, reunited VietNam, socialist Burma, Malaysia, Singapore, Indonesia, and the Philippines. The book not only provides insight into the past of this burgeoning region, but it offers a provocative view of the future as well. It suggests for instance that Japan, the present leader of the Pacific Rim, will eventually be overtaken by its neighbors, now engaged in a hectic pace of development (seen especially in the People's Republic of China, which has only just begun to compete as an exporter). The book concludes that the relations between the Chinese and the Japanese will determine the future of East Asia
Keywords: east asia; history